THE IMPACTS OF FINAL DEMAND OF INDONESIA’S EXPORTED PRODUCTS ON DOMESTIC INCOME AND EMPLOYMENT - Aditya P Alhayat (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2013)
Statistik perdagangan internasional dapat menyebabkan interpretasi yang kurang lengkap tentang pentingnya perdagangan internasional, terkait dengan sistem pencatatannya dan semakin meningkatnya globalisasi proses produksi barang. Studi ini bertujuan untuk mengestimasi sejauh mana perekonomian Indonesia bergantung pada permintaan akhir di suatu pasar ekspor tertentu dan dampaknya terhadap penciptaan pendapatan dan lapangan kerja ketika terjadi fragmentasi produksi global. Analisis ini menggunakan pendekatan global value chain dan Tabel Input-Output Dunia. Hasil studi menunjukkan bahwa nilai tambah dan lapangan kerja sebagai akibat dari pemenuhan permintaan akhir di negara maju lebih tinggi daripada yang dihasilkan dari pemenuhan permintaan akhir di negara berkembang. Peningkatan integrasi produksi di wilayah yang sama (Asia Timur atau ASEAN) dapat menjadi strategi yang efektif untuk mempengaruhi peningkatan pendapatan dan kesempatan kerja di Indonesia secara langsung dan tidak langsung.The conventional trade statistics may lead to an incomplete interpretation on the importance of international trade, due to its recording system and the increasing globalization of production process. The global value chain approach and the World Input Output Table were employed. This paper aims to estimate the extent to which Indonesia’s economy relies on the final demand of the particular export market in term of generating incomes and employment when the fragmentation of global production exists. The results show that value added and employments induced by final demand in advanced economies are higher than those generated by final demand in developing economies. Enhancing production integration within the same region (East Asia or ASEAN) can be an effective strategy to induce higher Indonesia’s income and employment directly and indirectly.